Patterns of Fluoride Intake from 36 to 72 Months of Age - Steven M. Levy, DDS, MPH; John J. Warren, DDS, MS; Barbara Broffitt, MS (Blackwell Synergy, 2003)
This paper reports on estimated daily fluoride intake from water by itself, beverages, selected foods, dentifrice, and dietary supplements, both individually and combined (mg and mg F/kg bw), among 785 children in the Iowa Fluoride Study from 36 to 72 months of age